A VHDL-based protocol controller for NCAP processors - Rossi, S. R.; Moreno, E. D.; Carvalho, A. A. de [UNESP]; Silva, Alexandre César Rodrigues da [UNESP]; Batista, E. A. [UNESP]; Prado, T. A. [UNESP]; Santos Filho, T. A. [UNESP] (Elsevier B.V., 2009)
This work presents the development of an IEEE 1451.2 protocol controller based on a low-cost FPGA that is directly connected to the parallel port of a conventional personal computer. In this manner it is possible to implement a Network Capable Application Processor (NCAP) based on a personal computer, without parallel port modifications. This approach allows supporting the ten signal lines of the 10-wire IEEE 1451.2 Transducer Independent Interface (TII), that connects the network processor to the Smart Transducer Interface Module (STIM) also defined in the IEEE 1451.2 standard. The protocol controller is connected to the STIM through the TII's physical interface, enabling the portability of the application at the transducer and network processor level. The protocol controller architecture was fully developed in VHDL language and we have projected a special prototype configured in a general-purpose programmable logic device. We have implemented two versions of the protocol controller, which is based on IEEE 1451 standard, and we have obtained results using simulation and experimental tests. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Transducer; Protocol controller; Interface; Programmable logic; IEEE 1451